FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Elfira Putri; Rahima Br Purba; Renny Maisyarah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to analyze the influence of Profitability, Liquidity and Leverage on audit delay in pharmaceutical companies listed on the IDX. The population of this research is 11 companies, while the sample used in this research is based on predetermined criteria, the number of pharmaceutical sector companies listed on the Indonesia Stock Exchange in 2019 - 2023 that have met the criteria in sampling is 10 companies. The number of years of observation used in this research is 5 years so the number of observations in this research is 50 observation sample units. The research results show that profitability has a partially negative and significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Liquidity has a positive and partially insignificant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Leverage has a negative and partially insignificant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Profitability, Liquidity and Leverage have a significant simultaneous effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange.